Revealing Widespread Misconception: A Multitier Science Instrument (MscI) to Assess Pre-Service Elementary Teachers' Understanding - Yulianawati, Dewi; Rochmah, Eliya; Jannah, Widia Nur; Fikriyah, Fikriyah; Septiany Rahayu, Fanny (Profesi Pendidikan Dasar, 2025)
Prior studies demonstrate that numerous pre-service teachers retain scientific misconceptions, and existing assessment instruments are inadequate for accurately distinguishing levels of comprehension. This research developed the Multitier Science Instrument (MScI), a reliable diagnostic tool for improving the evaluation of conceptual comprehension.  The research utilised the 4D model, which consists of four phases: defining, designing, developing, and disseminating. The study involved thirty-one pre-service elementary school teachers, with an average age of 19 years, at an Islamic university in Cirebon, Indonesia. CVR analysis and other statistical techniques evaluated the instrument's validity and reliability while analysing the distribution of misconceptions. The results demonstrate that the Multitier Science Instrument (MScI) possesses high validity, evidenced by a Content Validity Ratio of 0.966, surpassing the benchmark of 0.672, and robust reliability, as indicated by a Cronbach's alpha coefficient of 0.827.  The responses from participants were divided into four groups: sound understanding, partial understanding, misconceptions, and no understanding. Fluid statics exhibited the highest degree of misconceptions among the evaluated subjects.  These findings underscore the pressing necessity for enhanced diagnostic instruments in education.  Conventional assessment techniques, such as multiple-choice examinations and essay prompts, inadequately reflect the genuine depth of pre-service elementary educators' conceptual comprehension